Metalloid tellurium-doped graphene nanoplatelets as ultimately stable electrocatalysts for cobalt reduction reaction in dye-sensitized solar cells. (December 2016) - Jeon, In-Yup; Kim, Hong Mo; Kweon, Do Hyung; Jung, Sun-Min; Seo, Jeong-Min; Shin, Sun-Hee; Choi, In Taek; Eom, Yu Kyung; Kang, Sung Ho; Kim, Hwan Kyu; Ju, Myung Jong; Baek, Jong-Beom
Abstract: One feasible alternative to Pt catalyst in dye-sensitized solar cells (DSSCs) is metalloid tellurium (Te)-doped graphene nanoplatelets (TeGnPs). These were prepared by ball-milling graphite in the presence of Te crystals. Introduction of Te at the edges of TeGnPs was confirmed with various analytical techniques including time of flight secondary ion mass spectrometry (TOF-SIMS). The resultant TeGnPs are herein evaluated as counter electrode (CE) materials for the cobalt reduction reaction (CRR) in DSSCs. TeGnP-CE exhibits much lower charge transfer resistance ( R ct =0.15 Ω cm 2 ) than that ( R ct =1.77 Ω cm 2 ) of Pt-CE. More importantly, TeGnP-CE displays an extreme electrochemical stability for the Co(bpy)3 2+/3+ (bpy=2, 2'-bipyridine) redox couple even after 1000 potential cycles. The SM315-based DSSC fabricated with TeGnP-CE shows a better power conversion efficiency (PCE=11.58%) than that with Pt-CE (11.03%), suggesting that TeGnP-CE could be one of the best alternatives to Pt-CE in DSSCs. Graphical abstract: Tellurium-doped graphene nanoplatelets (TeGnPs) electrocatalysts for cobalt reduction reaction (CRR) in dye-sensitized solar cells (DSSCs) displayed much higher electrocatalytic activities with almost 'zero-loss' electrochemical stability than did Pt. Highlights: Tellurium (Te)-doped graphene nanoplatelets (TeGnPs) was, for the first time, prepared by mechanochemical reaction. TeGnPs were tested as a material for counter electrode (CE) in dye-sensitized solar cell (DSSC). TeGnPs showed much low charge transfer resistance, extreme electrochemical stability and high power conversion efficiency compared with conventional Pt-CE. The results suggested that TeGnPs can be one of the best alternatives to expensive Pt-CE.